Polyploid giant cancer cells and their role in the formation of resistance to therapeutic treatment - N. L. Vartanyan (IP Habib O.N., 2020)
The review considers the properties of polyploid giant tumor cells a new target for the development of cancer therapy. Various number of polyploid giant tumor cells are detected in almost all human solid tumors. Their number increases under the influence of hypoxia, radiation, and after chemotherapy. Previously, these cells were not considered to be worth studying as they do not proliferate and eventually die as a result of one of the cell death mechanisms action. Recent data have demonstrated that polyploid giant cells can give rise to daughter cells that possess tumorigenicity and are characterized as stem tumor cells. Giant tumor cells and daughter cells are involved in the processes of metastasis, recurrence, drug resistance formation and radio-resistance of tumors. The search is under way for molecular targets that could prevent the appearance or contribute to the elimination of previously formed polyploid giant tumor cells. The combination of traditional therapy that causes the death of proliferating tumor cells and allows their elimination, with the use of tools that could prevent the appearance of resistant polyploid giant cells and their daughter cells, can be the key to the effective treatment of malignancies.